Does Free-Text Information in Falls Incident Reports Assist to Explain How and Why the Falls Occurred in a Hospital Setting? - De Jong, Lex; Francis-Coad, J.; Waldron, N.; Ingram, K.; McPhail, S.; Etherton-Beer, C.; Haines, T.; Flicker, L.; Weselman, T.; Hill, A. (2018)
OBJECTIVE: The aim of this study was to explore whether information captured in falls reports in incident management systems could be used to explain how and why the falls occurred, with a view to identifying whether such reports can be a source of subsequent learnings that inform practice change. METHODS: An analysis of prospectively collected falls incident reports found in the incident management systems from eight Western Australian hospitals during a stepped-wedge cluster-randomized controlled trial. The falls reported occurred in a cohort of older hospital patients (mean age = 82 y) on rehabilitation wards. Data coded from free-text comments in the incident reports were analyzed using deductive content analysis. RESULTS: In the 493 analyzed falls incident reports, qualitative information describing aspects of the fall that clarified the patient, staff, and environment-related contributory factors was consistently low. Reports infrequently contained information about patients' and staff's call bell use behaviors (13%-19% of reports), fidelity of implementation of the care plan (8%) or environment-related factors such as bed settings (20%), and presence of clutter at the fall location (1%). The patients' account of the fall was present in less than 50% of reports, with an absence of concurrent text, which explained whether patient cognitive impairment was the reason for not obtaining this first-person account of the incident. CONCLUSIONS: Falls reports in hospital incident management systems may not capture adequate information to explain how and why falls occur. This could limit creation of effective feedback loops to drive quality improvement efforts and targeted practice change.